PENAMBAHAN PROBIOTIK LACTOBACILLUS ACIDOPHILUS DAN BIFIDOBACTERIUM SP TERHADAP ANALISIS USAHA AYAM PETELUR YANG DIINFEKSI ESCHERICHIA COLI - Khoirul Huda; Widya Paramita Lokapirnasari; Soeharsono Soeharsono (Universitas Galuh Ciamis, 2019)
The purpose of this study was to determine the use of probiotics Lactobacillus acidophilus and Bifidobacterium sp on variable cost, income and profit layers hens was infected with Escherichia coli. About 120 layers at 25 weeks of age were randomized into six treatments. The treatment consisted of factors a (infection and non-infection Escherichia coli) and factor b (basal feed, AGP and probiotics). The results of the study gave probiotics an effect (p <0.05) on variable cost, income and profit. Infection factors have an effect (p <0.05) on income and profit, but have no effect (p> 0.05) on variable cost. There was interaction between probiotic and infection factors (p <0.05) on income and profit, but there was no interaction (p> 0.05) between probiotic and infection factors on variable cost. The highest variable cost was found in the treatment of non-infectious probiotics is Rp 13.594, the highest income was treated with non-infectious probiotics is Rp 26.564, the highest profit was treated with non-infectious probiotics is Rp 12.969. It could be concluded that the administration of probiotics can produce good production performance.